Implementasi Sistem Informasi Manajemen Pendidikan (SIMP) Di Pondok Pesantren Tahfidzul Qur’an Ad Diin - Fatwai Nasikhah; Ali Muhdi (CV. ITTC INDONESIA, 2026)
This study examines the implementation of Education Management Information Systems (EMIS) at Pondok Pesantren Tahfidzul Qur'an (PPTQ) Ad Diin, Kuwarasan, Kebumen, focusing on five platforms mandated by the Indonesian Ministry of Religious Affairs: EMIS LPQ, SIPDAR PQ, SIMBA, SIKAP, and APKITA. The core issues addressed include the varying levels of platform adoption, the benefits gained, and the obstacles encountered during implementation. This research aims to describe the implementation process comprehensively, analyze its benefits for institutional management, and identify the challenges faced. A qualitative case study approach was employed, with data collected through participatory observation over approximately eight weeks, semi-structured in-depth interviews with the pesantren's director, senior teachers, and system operators, and documentation. Data were analyzed using Miles, Huberman, and Saldana's interactive model and validated through source and technique triangulation. The findings reveal that all five platforms are actively utilized, with EMIS LPQ and SIPDAR PQ being the most intensively used. Key benefits include improved institutional data accuracy, streamlined aid applications via SIMBA, facilitated teacher incentive submissions through SIKAP, and digitalized student financial management via APKITA. However, significant challenges persist, namely an overreliance on one to two operators, unstable internet infrastructure, low data-entry awareness among staff, and the absence of continuous operator training.